Pengaruh Implementasi Sistem Manajemen Rumah Sakit (SIMRS) Dan Beban Kerja Perawat Terhadap Kinerja Perawat Di Ruang Dahlia RSUP dr. Soeradji Tirtonegoro Klaten - Didik Setiyawan; Eddy Hermawan Hasudungan Panjaitan; Sukiman Sukiman (Journal of Innovative and Creativity, 2025)
The purpose of this study is to determine the influence of the implementation of the hospital management system (SIMRS) and the workload of nurses on the performance of nurses in the Dahlia Room of the Central General Hospital, Dr. Soeradji Tirtonegoro Klaten The method used is a quantitative and descriptive research method. The sampling technique with the entire population of nurses in the Dahlia room was 121 respondents. Based on the results of the examination, H0 was rejected and H1 was accepted. This can be seen from the calculated F value, which is 42,791. Meanwhile, the resulting significance value is 0.000 which is smaller than 0.05. Thus, it can be concluded that this multiple regression model is feasible to use, and the hospital implementation variable (SIMRS) and the nurse workload have a simultaneous influence on the nurse performance variable. The conclusion based on the results of the study on the effect of the implementation of the hospital management system (SIMRS) and workload on the nurse staff in the Dahlia Room of the Central General Hospital Dr. Soeradji Tirtonegoro Klaten with a total of 72 respondents can be concluded that: There is a significant positive influence on the implementation of the hospital management system on the workload of nurses in the Dahlia Room of the Central General Hospital Dr. Soeradji Tirtonegoro Klaten, There is a significant positive influence on the workload on the performance of nurses in the Dahlia Room of the Central General Hospital Dr. Soeradji Tirtonegoro Klaten, There is a significant positive influence on the implementation of the hospital management system (SIMRS) and the workload on the performance of nurses in the Dahlia Room of the Central General Hospital General Center Dr. Soeradji Tirtonegoro Klaten